Study on the evolution from α-GaOOH to α-Ga2O3 and solar-blind detection behavior of an α-GaOOH/α-Ga2O3 heterojunction. Issue 9 (15th February 2022) - Zhang, Yanan; Jiao, Shujie; Zhang, Junhua; Liu, Shuo; Wang, Dongbo; Gao, Shiyong; Wang, Jinzhong
Abstract : The photoelectrochemical detectors based on the GaOOH/Ga2 O3 heterojunction have a significantly improved photo detection performance compared with GaOOH and Ga2 O3 detectors. Abstract : A GaOOH/Ga2 O3 heterojunction was obtained by a one-step annealing treatment at a certain temperature. The solar blind photoresponse performance of the GaOOH/Ga2 O3 heterojunction was characterized through photoelectrochemical detectors, providing a simple and effective method for pure solar-blind ultraviolet detection. The results showed that the maximum responsivity of the α-GaOOH/α-Ga2 O3 heterojunction detector is 0.29 mA W −1 at 250 nm, which is 370% and 145% higher than that of the α-GaOOH and α-Ga2 O3 detectors, respectively. The calculated solar-blind/visible detection ratio and light-to-dark current ratio of the detector are also significantly improved compared with the α-Ga2 O3 and α-GaOOH detectors, reflecting better pure solar-blind ultraviolet detection performance. The photoresponse mechanism has been studied systemically.